(untitled) (Innovative professional education, 2023)
The article analyzes the interactive forms, methods, techniques, and technologies of vocational training that are recognized as the most effective and, for many years, have been holding the predominant position among the recommended approaches for use in the educational process. Based on my own experience of teaching environmental disciplines, I have identified a list of interactive methods that can be used in the educational process to significantly increase the percentage of material perception by higher education students. This approach allows you to intensify the learning process, make it more interesting, and most importantly, more effective.